Exploring Project-Based Teaching for Engaging Students’ Mathematical Learning - Tyata, Raj Kumar; Dahal, Niroj; Pant, Binod Prasad; Luitel, Bal Chandra (Mathematics Education Forum Chitwan, 2021)
The declining interest of learners in mathematics in the learning process has resulted in poor achievement (Yeh et al., 2019). To get rid of these poor achievements, we explored project-based teaching in four topical areas (e.g., mathematical concepts of coordinate geometry, trigonometry, sequence, and series) in the school mathematics. This paper results from observing changes in engagement of learners in learning mathematics by motivating them through the project-based learning (PBL) guided by two theories – knowledge constitutive interests (Habermas, 1972), and collaborative and cooperative learning under the paradigms of interpretivism and criticalism. In this ethos, PBL is an “engaging and learner-directed approach that provides equal opportunities for students to explore their knowledge and understanding” (Thomas, 2000, p. 12). More specifically, we adopted the 'action research' method with the secondary level students (Grade IX) of one of the institutional schools in their classrooms. The information was collected by observing and recording the changes seen in consecutive seventeen days. The research landed that project-based learning is an appropriate pedagogy for engaged learning. The study revealed that the students were motivated while they got opportunities to interact in the projects. Moreover, the findings show that PBL is helpful to engage the learners through questioning, pair/group discussion, discovery learning, and concept mapping.